PENGARUH SISTEM PENGENDALIAN INTERN DAN KOMPETENSI APARATUR DESA TERHADAP AKUNTABILITAS DANA DESA - Nispa Sari Sari; Rifqa Ayu Dasila; Sahrir (Universitas Islam Negeri Alauddin Makassar, 2022)
Accountability is very important for the Village Government, this is because it involves responsibility for managing village funds in an efficient, effective, fair, and transparent manner by involving the community. This study aims to determine the effect of the internal control system and the competence of the village apparatus on the accountability of village funds. The research was conducted at the Village Office in the Kecamatan Ponrang Selatan. The population is a village in the Kacamatan Ponrang Selatan. Based on the purposive sampling method, the research sample used was 64 respondents. The data analysis technique in this study is multiple linear regression. The results showed that the internal control system had a significant positive effect on the accountability of village funds, the competence of the village apparatus had a significant positive effect on the accountability of village funds.